Mcgraw-Hill Encyclopedia of Science and Technology: Volume 14: Tow-Zyt (New York Mcgraw- Hill Book Company, Inc., 1971)
An International Reference Work in Fifteen Volumes Including an Index
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; Science -- Encyclopedias; General; Technology -- Encyclopedias